Islamic Banks as Agents of Economic Growth: An Econometric Analysis of Islamic Economy - Rodrigo Bochner (AL-FALAH : Journal of Islamic Economics, 2025)
This study scrutinizes the role of Islamic banks as dynamic agents fostering economic growth underpinned by Shariah-compliant principles, notably risk-sharing, prohibition of interest (riba), and avoidance of excessive uncertainty (gharar). Utilizing advanced econometric methodologies including stationary tests (ADF, KPSS), Johansen co-integration error correction mechanisms, Granger causality, fully modified ordinary least squares (FMOLS), and quantile regressions on a broad panel dataset from 1990– 2023 covering Muslim-majority economies and GCC , the analysis confirms a statistically positive nexus between Islamic banking development and macroeconomic growth indicators such as GDP and capital formation. Incorporating mathematical models of profit-and-loss sharing (PLS) and asset-backed finance within stochastic optimization frameworks, elucidates the mechanisms by which Islamic finance bolsters financial stability, deepens financial inclusion, and promotes sustained development. The findings underscore the critical moderating impact of inflation and economic policy uncertainty, highlighting the necessity of macroeconomic stability to optimally leverage Islamic finance’s potentials. Policy recommendations include enhancing Shariah governance, expanding inclusive finance infrastructure, and reinforcing regulatory environments. This paper advances the literature by integrating Islamic economic theory with econometric modeling to delivering an interdisciplinary framework for future research, policy making and proposes a new understanding from an econometric perspective about impact of islamics economics in economic development.